2019
DOI: 10.17245/jdapm.2019.19.5.245
|View full text |Cite
|
Sign up to set email alerts
|

Dental complications associated with neonatal intubation in preterm infants

Abstract: This paper describes the potential oral complications in preterm infants who have undergone orotracheal intubation. Neonatal intubation may have adverse effects on the developing deciduous teeth, oral soft tissues, and even the permanent teeth. However, endotracheal intubation may be essential for the survival of premature infants, owing to incomplete tracheal development. Excessive pressure to the oral tissue must be avoided, in cases where orotracheal intubation is inevitable. Moreover, the potential oral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Outcomes of several previous European studies suggest that individuals who experienced preterm birth tend to show malocclusions due to disharmonious facial growth [ 37 ]. Although controversial, many previous malocclusion studies were based on the assumption that life-supporting equipment maintained in the oral cavity of preterm infants is the principal causal contributor to malocclusions [ 38 , 39 ]. However, the findings here indicate that a more plausible pathophysiology for faulty facial bone development is impaired breathing, leading to IH that triggers exaggerated sympathetic outflow at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of several previous European studies suggest that individuals who experienced preterm birth tend to show malocclusions due to disharmonious facial growth [ 37 ]. Although controversial, many previous malocclusion studies were based on the assumption that life-supporting equipment maintained in the oral cavity of preterm infants is the principal causal contributor to malocclusions [ 38 , 39 ]. However, the findings here indicate that a more plausible pathophysiology for faulty facial bone development is impaired breathing, leading to IH that triggers exaggerated sympathetic outflow at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Subglottic stenosis is a late sequelae for endotracheal intubation [ 110 , 111 ]. Numerous complications in the oral cavity are caused by tracheal intubation during oral development such as alveolar or palatal grooving, palatal deformation, defective development of enamel, tooth malformation, displacement of tooth germ, eruption sequence, crossbite, oral commissure defect, temporomandibular joint injury, tongue injury, and incorrect pronunciation [ 112 ]. The possibilities of complications increase with an increasing number of intubations attempts and are reduced with use of paralytic medications and intubator training [ 106 , 107 ].…”
Section: Endotracheal Tube (Ett)mentioning
confidence: 99%
“…The most prevalent oral complications are hypoplasia and opacities of the dental enamel in primary teeth [ 11 14 ]. Several studies have reported the deleterious effects of preterm birth on oral health and development, such as crown dilaceration [ 15 ], palatal distortions [ 16 ], delayed tooth eruption [ 17 ], and dental caries [ 18 ]. Immature neurodevelopment and endotracheal intubation may cause dental occlusion and influence jaw symmetry [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the deleterious effects of preterm birth on oral health and development, such as crown dilaceration [ 15 ], palatal distortions [ 16 ], delayed tooth eruption [ 17 ], and dental caries [ 18 ]. Immature neurodevelopment and endotracheal intubation may cause dental occlusion and influence jaw symmetry [ 16 , 19 ]. Early nutritional support is important for preterm infants because it influences long-term health and development [ 20 ], can reduce the risk of impaired growth, and can limit the need for high levels of nutrient supplementation after discharge.…”
Section: Introductionmentioning
confidence: 99%